OPTIMIZATION OF THE ROLE OF THE GENERAL ELECTION COMMISSION OF CIAMIS DISTRICT IN SOCIALIZATION OF GENERAL ELECTION OF 2018 REGIONAL HEADS TO BEGINNER VOTERS: Descriptive Study of Beginner Voters in Ciamis District in 2018 Regent and Vice Regent Election of Ciamis - Gelar Pangestu; Kiki Endah (JGSRD: Journal of Government Science and Rural Development, 2020)
The role of the General Election Commission in organizing elections is not merely related to the parties participating in the election, but also must provide political socialization to the public as voters in the election. Voters are Indonesian citizens who have reached the age of 17 (seventeen) years old. In fact socialization so far only targeted beginner voters in school. The purpose of this study was to develop a program to carry out socialization carried out by the Ciamis Regency KPU to novice voters in order to gain knowledge, beliefs and political attitudes. This study used descriptive qualitative method. The results of this study indicate that the role of the Ciamis Regency Election Commission in the socialization of the 2018 regional head elections to novice voters has not been optimal. This can be seen from the number of beginner voters who do not yet know and get knowledge, beliefs and political attitudes from the socialization carried out. Socialization needs to be done with various methods other than direct communication in the form of face-to-face or lectures. In addition to the socialization of using media, including online media. There is a need for continued coordination and collaboration with various parties, both government agencies, schools, and parents in socializing the importance of using their right to vote and participating in the successful holding of regional elections.